1983
DOI: 10.1002/lary.1983.93.10.1337
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy for Persistent Tumor at the Surgical Margin in Head and Neck Cancers

Abstract: Seventy-two patients with a carcinoma of the head and neck, who were treated with surgery and postoperative irradiation, were reviewed to determine the local recurrence rates and survival in patients with inadequate surgical margins. Tumor recurrence rate was 31% for patients with microscopic tumors at resection margins and 50% for those with macroscopic tumor. Actuarial 3-year survival for these patients was 71% and 43%, respectively. All 4 patients who were irradiated later than 6 weeks after surgery develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 13 publications
(7 reference statements)
0
18
0
3
Order By: Relevance
“…Perineural invasion (PNI), lymphovascular invasion, T3 to T4 disease, or N2 disease are considered intermediate‐risk factors and adjuvant RT alone is typically offered to patients with these findings. Positive margins or extracapsular extension (ECE) are considered high‐risk factors and adjuvant chemoradiotherapy (CRT) has a demonstrated survival benefit compared to RT alone in this population …”
Section: Introductionmentioning
confidence: 99%
“…Perineural invasion (PNI), lymphovascular invasion, T3 to T4 disease, or N2 disease are considered intermediate‐risk factors and adjuvant RT alone is typically offered to patients with these findings. Positive margins or extracapsular extension (ECE) are considered high‐risk factors and adjuvant chemoradiotherapy (CRT) has a demonstrated survival benefit compared to RT alone in this population …”
Section: Introductionmentioning
confidence: 99%
“…Surgery and radiotherapy are the treatment options for the localized or regional disease. 3,4 Many patients with head and neck cancer are submitted to high doses of radiotherapy in large areas including oral cavity, maxilla, mandible and salivary glands. Despite having the advantage of preserving the tissue structure, radiotherapy causes many adverse reactions in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Delaying the initiation of irradiation beyond 6 weeks after operation increases the recurrence rate (10,23). It has been suggested that the time interval between surgery and radiation therapy be less than 6 weeks (lo), or that irradiation should begin as soon as healing is adequate ( I ) .…”
Section: Discussionmentioning
confidence: 99%